2016
DOI: 10.4306/pi.2016.13.2.239
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Relations of Smoking Status, Depression, and Suicidality in Korea: Findings from the Korea National Health and Nutrition Examination Survey 2008-2012

Abstract: ObjectiveAs mental health problems may play an important role in initiating and maintaining cigarette smoking in females and there are an increasing number of female smokers, we evaluated the relationship between smoking status and mental health problems including depression and suicide ideation in women in Korea.MethodsWe analyzed the 5-year cumulative data (19 years of age or older, n=32,184) from the Korean National Health and Nutrition Examination Survey (KNHANES) conducted from 2008 to 2012. Logistic regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 39 publications
3
8
1
Order By: Relevance
“…Comparing the results between sexs, the use of ECs among female students shows a higher risk of alcohol consumption and problem drinking than in male students. This sex difference has also been found in other studies that analyzed the association between smoking and other problem behaviors in Korean students [17]. In Korea, male students tend to have problem behaviors such as smoking or drinking, whereas female students tend to do the same but in small clusters.…”
Section: Discussionsupporting
confidence: 78%
“…Comparing the results between sexs, the use of ECs among female students shows a higher risk of alcohol consumption and problem drinking than in male students. This sex difference has also been found in other studies that analyzed the association between smoking and other problem behaviors in Korean students [17]. In Korea, male students tend to have problem behaviors such as smoking or drinking, whereas female students tend to do the same but in small clusters.…”
Section: Discussionsupporting
confidence: 78%
“…Therefore, multivariate analysis should be performed to define if these factors are independent risk factors for COPD. Marital status was related to smoking history in a previous study,13 whereas the present study showed that marital status was not significantly associated with COPD; this result should be re-judged based on previous studies because the total number of unmarried subjects was small (n=41; representing 419,691 subjects; 1.3% of the total number of subjects) in this study.…”
Section: Discussioncontrasting
confidence: 63%
“…Our findings suggest that more than noise exposure, exposure to vibration had a prominent effect on insomnia. In addition, the prevalence of insomnia was higher in females than in males, which is consistent with previous findings that women are more vulnerable to mental health problems than men [25,26]. However, with the exception of simultaneous noise and vibration exposure, the OR of insomnia was higher in males than females.…”
Section: Discussionsupporting
confidence: 90%